Retinal Gene Therapy: Surgical Vector Delivery in the Translation to Clinical Trials - Ochakovski, G. Alex; Bartz-Schmidt, K. Ulrich; Fischer, M. Dominik (Frontiers in Neuroscience, 2017)
An exceptionally high number of monogenic disorders lead to incurable blindness, making them targets for the development of gene-therapy. In order to successfully apply therapeutic vector systems in vivo, the heterogeneity of the disease phenotype needs to be considered. This necessitates tailored approaches such as subretinal or intravitreal injections with the aim to maximize transduction of target cell populations, while minimizing off-target effects and surgical complications. Strategic decisions on parameters of the application are crucial to obtain the best treatment outcomes and patient safety. While most of the current retinal gene therapy trials utilize a subretinal approach, a deeper understanding of the numerous factors and considerations in choosing one delivery approach over the other for various ocular pathologies could lead to an improved safety and treatment efficacy. In this review we survey different vector injection techniques and parameters applied in recent retinal (pre-)clinical trials. We explore the advantages and shortcomings of each delivery strategy in the setting of different underlying ocular pathologies and other relevant factors. We highlight the potential benefits for patient safety and efficacy in applying those considerations in the decision making process.